The positive and negative aspects of parentification: an integrated review - Masiran, Ruziana; Ibrahim, Normala; Awang, Hamidin; Lim, Poh Ying (Elsevier, 2022)
The literature suggests that some children at increased risk of parentification, which includes children of chronically ill or substance-misusing parents and children of divorced or migrant parents. Despite the necessity for some children to assume adult roles, parentification is potentially harmful. This paper aims to: (i) investigate the parentification concept and outcomes and (ii) summarize the components that render parentification adaptive in children. Articles were retrieved from Scopus, PubMed, Dimensions AI, Google Scholar, and reference list tracking using the keywords “parentification” and “parentification AND children”. A critical review was performed with a narrative approach to synthesize the 61 included studies to determine the existing knowledge and identify research priorities within the field of parentification. The findings were reported based on the Literature Review Synthesis Process and the Scale for the Assessment of Narrative Review Articles (SANRA). The experience of parentification could be adaptive and empowering for children. The potential components of adaptive parentification included emotional support, supportive and positive relationships with siblings and grandparents, parents openly delegating the roles to each child, having age-appropriate roles, parental support and validation, and children’s positive appraisal and perception of the role-taking.